Pharmacogenetics of Antipsychotic-Induced Movement Disorders as a Resource for Better Understanding Parkinson’s Disease Modifier Genes - Greenbaum, Lior; Lerer, Bernard (Frontiers in Neurology, 2015)
Antipsychotic-induced movement disorders are major side effects of antipsychotic drugs among schizophrenia patients, and include antipsychotic-induced parkinsonism (AIP) and tardive dyskinesia (TD). Substantial pharmacogenetic work has been done in this field, and several susceptibility variants have been suggested. In this paper, the genetics of antipsychotic-induced movement disorders is considered in a broader context. We hypothesize that genetic variants that are risk factors for AIP and TD may provide insights into the pathophysiology of Parkinson's disease (PD). Since loss of dopaminergic stimulation (albeit pharmacological in AIP and degenerative in PD) is shared by the two clinical entities, genes associated with susceptibility to AIP may be modifier genes that influence clinical expression of PD sub-phenotypes, such as age at onset, disease severity or rate of progression. This is due to their possible functional influence on compensatory mechanisms for striatal dopamine loss. Better compensatory potential might be beneficial at the early and later stages of the PD course. AIP vulnerability variants may also be related to latent impairment in the nigrostriatal pathway, affecting its functionality, and leading to subclinical dopaminergic deficits in the striatum. Susceptibility of PD patients to early development of L-dopa induced dyskinesia (LID), is an additional relevant sub-phenotype. LID may share a common genetic background with TD, with which it shares clinical features. Genetic risk variants may predispose to both phenotypes, exerting a pleiotropic effect. According to this hypothesis, elucidating the genetics of antipsychotic-induced movement disorders may advance our understanding of multiple aspects of PD and it clinical course, rendering this a potentially rewarding field of study.